The response of suction caissons to multidirectional lateral cyclic loading in sand over clay. (15th December 2018) - Zhu, Fangyuan; Bienen, Britta; O'Loughlin, Conleth; Morgan, Neil; Cassidy, Mark Jason
Abstract: Offshore wind turbines and their foundations experience loading from varying directions, yet understanding of the effect of changes in the direction of applied cyclic loading on foundation response remains limited. This study investigates the behaviour of a suction caisson foundation in sand over clay under various types of multidirectional cyclic loading. The findings are significant: although the caisson rotation (or tilt) is affected by changes in load direction, the caisson rotation is less than that in a unidirectional test with the same cyclic load magnitude and symmetry, meaning that a unidirectional test may serve as a conservative estimate of caisson rotation for multidirectional loading. This contrasts with previous findings for monopiles in sand, where prediction of the accumulated displacement based on unidirectional cyclic loading was substantially un-conservative for multidirectional loading. Changes in unloading stiffness due to changes in load direction are slight, varying by an amount that is no greater than the change measured over the course of a unidirectional test. Foundation stiffness and ultimate capacity following multidirectional cyclic loading are largely unaffected, unlike unidirectional cyclic loading, where consolidation of the clay layer improves both the stiffness and capacity. Highlights: Suction caissons as monopod foundations for offshore wind turbines. The behaviour of a suction caisson under multidirectional lateral cyclic loading is investigated. Changes in caisson rotation, caisson-soil stiffness and ultimate capacity due to variations in load direction are discussed. A method is used to predict the relationship between caisson rotation and cycle number.